2022
DOI: 10.3389/fcvm.2022.1053697
|View full text |Cite
|
Sign up to set email alerts
|

5mC modification patterns provide novel direction for early acute myocardial infarction detection and personalized therapy

Abstract: BackgroundMost deaths from coronary artery disease (CAD) are due to acute myocardial infarction (AMI). There is an urgent need for early AMI detection, particularly in patients with stable CAD. 5-methylcytosine (5mC) regulatory genes have been demonstrated to involve in the progression and prognosis of cardiovascular diseases, while little research examined 5mC regulators in CAD to AMI progression.MethodTwo datasets (GSE59867 and GSE62646) were downloaded from Gene Expression Omnibus (GEO) database, and 21 m5C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
(48 reference statements)
0
0
0
Order By: Relevance
“…Yiqun G. et al [149] revealed a significant influence of 5mC regulators on the diagnostic accuracy of distinguishing stable coronary artery disease (CAD) from acute myocardial infarction (AMI). We identified nine key 5mC regulators (DNMT3B, MBD3, UHRF1, UHRF2, NTHL1, SMUG1, ZBTB33, TET1, and TET3) that could serve as potential latent biomarkers in AMI.…”
Section: Biomarkers Of Cadmentioning
confidence: 99%
“…Yiqun G. et al [149] revealed a significant influence of 5mC regulators on the diagnostic accuracy of distinguishing stable coronary artery disease (CAD) from acute myocardial infarction (AMI). We identified nine key 5mC regulators (DNMT3B, MBD3, UHRF1, UHRF2, NTHL1, SMUG1, ZBTB33, TET1, and TET3) that could serve as potential latent biomarkers in AMI.…”
Section: Biomarkers Of Cadmentioning
confidence: 99%